On Adam Mickiewicz's theory of romanticism - Novruzov, Rafig (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
This article is devoted to considering the views of the famous Polish classic Adam Mickiewicz on oriental romanticism. It is known that the Polish poet is considered the founder of Polish romanticism. At the same time, the beginning of this trend in Mickiewicz's poetry was laid by sonnets on eastern themes, which later found continuation in other forms of creativity. The creation of the West-Eastern synthesis was not accidental for his work. The fact is that even before the appearance of the cycle of poems on eastern motives, Mickiewicz wrote two unique articles ("Goethe and Byron", "On Romantic Poetry"), in which he tries to compare not only the poetic principles of two brilliant representatives of German and English literature, who influenced his work, but also to trace the origin and development of romanticism in world literature. These two articles are the object of this study. The analysis aims to determine the basic principles of the Polish poet's approach to the works of Goethe and Byron, to identify his views on the history of the origin and development of the romantic movement in world literature, and thereby establish his principles of Orientalism. The study concludes that the aforementioned theoretical works defined the eastern aspect of Mickiewicz’s romanticism and influenced his further work.